When representativeness matters: reflections on racism, identity valuation and Basic Education (Práxis Educativa, 2022)
This article presents reflections from experiences in school daily life involving the theme of black identity. The theoretical discussion contemplates the representativeness and impacts of the structural racism; in how the whiteness pact, black epistemicide and racism affect and cause fissures on the construction of the black community identity. We incorporated as methodological path the contributions of escrevivências (writing and experiences), by Evaristo (1995), a term that also figures as a methodological path. Considering escrevivência as a writing of us, we bring the writing of us constituted in interaction with children and adolescents of Basic Education, incorporated into teaching and research in day care and school. Among other issues, we found that the black teacher committed to ethnic-racial education can potentially assist in the positive construction of the identity of black children and adolescents in the fight against racism, in a country with a historical past-present of enslavement as striking as the one in Brazil.Keywords: Representativeness. Anti-racist education. Race.